lncRNA-Triggered Macrophage Inflammaging Deteriorates Age-Related Diseases - Lulingxiao Nie; Peng Zhang; Qian Wang; Xinyi Zhou; Qi Wang (Mediators of Inflammation)
Aging and age-related diseases (ARDs) share basic mechanisms largely involving inflammation. A chronic, low-grade, subclinical inflammation called inflammaging occurs during aging. Autophagy defects, oxidative stresses, senescence-associated secretory phenotypes (SASPs), and DNA damage generally contribute to inflammaging and are largely regulated by numerous lncRNA through two-level vicious cycles disrupting cellular homeostasis: (1) inflammaging and the cellular senescence cascade and (2) autophagy defects, oxidative stress, and the SASP cascade. SASPs and inflammasomes simultaneously cause inflammaging. This review discusses the involvement of macrophage inflammaging in various ARDs and its regulation via lncRNA. Among macrophages, this phenomenon potentially impairs its immunosurveillance and phagocytosis mechanisms, leading to decreased recognition and clearance of malignant and senescent cells. Moreover, SASPs extracellularly manifest to induce paracrine senescence. Macrophage senescence escalates to organ level malfunction, and the organism is more prone to ARDs. By targeting genes and proteins or functioning as competing endogenous RNA (ceRNA), lncRNA regulates different phenomena including inflammaging and ARDs. The detailed mechanism warrants further elucidation to obtain pathological evidence of ARDs and potential treatment approaches.